1993
DOI: 10.1046/j.1365-2648.1993.18091429.x
|View full text |Cite
|
Sign up to set email alerts
|

An international approach to master's‐level preparation for clinical nurse specialists*

Abstract: Nursing is seen as being increasingly a research-based profession with a developing knowledge base that demands a continuing programme of education. This is necessary to enable the practitioner to function with the level of expertise and skill required in today's health care systems. There have been repeated calls for and developments in the establishment of a higher-education approach to nursing, with degree courses for the advanced practitioner. It is also argued that in terms of the European perspective the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The general consensus in Australia and overseas in the countries, where there is an equivalent position (e.g. USA, UK, Hong Kong) (Davis 1993, Appel et al. 1996, Coyne 1996, Chang & Wong 2001), is that the major foci (domains) of the role of the CNC are clinical practice, consultation, education and research (Dawson et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The general consensus in Australia and overseas in the countries, where there is an equivalent position (e.g. USA, UK, Hong Kong) (Davis 1993, Appel et al. 1996, Coyne 1996, Chang & Wong 2001), is that the major foci (domains) of the role of the CNC are clinical practice, consultation, education and research (Dawson et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Terms such as analysis, critical thinking, synthesis of information, establishing priorities, reflection and creativity have been used to describe advanced practice (Davis, 1993) and claims are made that these are achievable through postgraduate education. However, objectivity in measurement remains problematic (Davis, 1993). The difficulties associated with conducting experimental research into ascertaining the effects of education in general on clinical practice are well-documented (Davies et al, 1997;Meah & Luker, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The University of Ulster has developed an integrated system of postgraduate education for nurses with the opportunity for students to progress as far as they are able or wish, exiting with a Postgraduate Diploma in Advanced Nursing or Midwifery, a Master of Science m Advanced Nursmg or Midwifery, or a Doctor of Nursing Science (DNSc) It incorporates both the study of nursing theory and practice, and the development of competence m research The first students will be ready to transfer to the DNSc stage of the programme in October 1995, if they achieve the required standard m their work to that point This programme is believed to be the first leading to a Doctor of Nursing Science ui Europe and is possibly the first integrated programme of this type in the world Individual master's courses in nursmg are now offered in a number of universities m the UK, some of them with strong European links (Davis 1993) The majonty ofthese emphasize administration and education (Armstrong-Esther & Myco 1987) although some are now focusmg on specialist practice Master's and DNSc programmes are Correspondence Professor f RJ* Boore, Nursing and Community Health Research Unit, University of Ulster, Coleraine, Co Londonderry BT52 ISA Northern Ireland email fRPBOOREQulst ac uk particularly well developed in North America and McKevitt (1986) reported that master's programmes had focused primarily on preparation for clinical and functional roles m nursing, possibly because of the increase in the number of doctoral programmes with a strong research emphasis This course of study has been designed within the United Kingdom higher education system, with its unique charactenstics, and it aims to mtegrate closely development for clinical practice with the acquisition of research expertise to a high level Planned withm the UK, it takes account of the specific needs of the nursing profession and the health care service withm this country However, as the first such programme withm the island of Ireland, it is intended to meet the needs of nurses fi-om the Republic of Ireland, as well as from Northern Ireland, and it is considered that the core content and the fiexibility planned into this programme makes it emmently smtable for other international students…”
Section: Introductionmentioning
confidence: 99%